Socialization of Occupational Safety and Health in the Kemiri Village Community in an Effort to Become a K3 Caring Village - Moch Sahri; Octavianus Hutapea; Friska Ayu; Muslikha Norma Romadhoni; Merry Sunaryo; Ratna Ayu Ratri Wardhani (UNUSA Press, 2024)
Socialization of occupational safety and health (OSH) is an important effort to raise community awareness about the importance of implementing OSH principles in the workplace, especially in villages with a high potential for accidents and work-related illnesses. This article examines the implementation of an OSH socialization program in Kemiri Village, aimed at fostering a strong OSH culture and creating an OSH-conscious village. The methods used in this study include observation, interviews, and the distribution of questionnaires to village residents. The research results indicate that the community's understanding of OSH remains low, with numerous cases of workplace accidents occurring due to a lack of knowledge and awareness of safety importance. The socialization program involved training, seminars, and outreach activities that engaged all community members. As a result of the socialization efforts, there was a significant increase in the community's knowledge and awareness of OSH. The community became more proactive in implementing preventive measures, leading to a reduction in workplace accident rates in the village. These findings suggest that effective OSH socialization efforts can create a safer and healthier working environment and encourage the establishment of an OSH-conscious village.